KAJIAN KETERSEDIAAN DAN KEBUTUHAN LAHAN TEMPAT PEMAKAMAN UMUM DI DISTRIK SARMI, KABUPATEN SARMI - Ronaldo Ruwayari, Daniel; Manalu, Janviter; Mujiati (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2025)
The availability and need for land for Public Cemeteries (TPU) is becoming an i ncreasingly urgent issue,especially in areas experiencing population growth such as Sarmi District, Sarmi Regency. This study aims toevaluate the current availability of TPU land, plan land use patterns in accordance with the Regional SpatialPlan (RTRW), and analyze local government involvement in TPU management. The research approach used isdescriptive quantitative by utilizing primary and secondary data. Data collection techniques included fieldobservations, interviews and analysis of policy documents. Data analysis was conducted using the GeographicInformation System (GIS) method to identify alternative locations for new cemeteries and the geometricformula to project land requirements. The results show that TPU Mararena still has a land capacity of 1,434m², while TPU Sarmi Kota has exhausted its capacity with a total area of 14,051 m². Projections of landrequirements show the need for a new location with an area of around 10,000 m² to meet the needs of thecemetery in the long term. The new site needs to be designed based on spatial criteria, such as accessibility,integration of green spaces, and sustainability of management. This research emphasizes the importance ofcross-sectoral coordination between local governments, communities and customary institutions to createmore effective and environmentally friendly TPU management. New TPUs that support ecological, social, andaesthetic functions can be a sustainable solution to overcome the limitations of cemetery land in the future.